An introduction to probabilistic fault displacement hazard analysis in site evaluation for existing nuclear installations. (IAEA-TECDOC ;, 2021)
"Probabilistic fault displacement hazard analysis (PFDHA) is a relatively new methodology, and actual examples of applications are quite limited. The current publication provides an introduction to probabilistic approaches to fault displacement hazard assessment with reference to relevant IAEA safety standards. It delineates the most important aspects of PFDHA (including up to date practices, open problems, and challenging issues) within a coherent framework. The information provided will be valuable not only for Member States when applying PFDHA to the site safety assessment of existing installations, but also for nuclear power plant operating organizations, regulatory bodies, vendors, technical support organizations and researchers working in the area of seismic hazard assessment."--Publisher's description.